First transcriptomic insight into the reprogramming of human macrophages by levan-type fructans - (:unkn) unknown (My University, 2023)
Based on stimuli in the biological milieu, macrophages can undergo classical activation into the M1 pro-inflammatory (anti-cancer) phenotype or to the alternatively activated M2 anti-inflammatory one. Drug-free biomaterials have emerged as a new therapeutic strategy to modulate macrophage phenotype. Among them, polysaccharides polarize macrophages to M1 or M2 phenotypes based on the surface receptors they bind. Levan, a fructan, has been proposed as a novel biomaterial though its interaction with macrophages has been scarcely explored. In this study, we investigate the interaction of non-hydrolyzed and hydrolyzed Halomonas levan and its sulfated derivative with human macrophages in vitro. Viability studies show that these levans are cell compatible. In addition, RNA-sequencing analysis reveals the upregulation of pro-inflammatory pathways. These results are in good agreement with real time-quantitative polymerase chain reaction that indicates higher expression levels of C-X-C Motif Chemokine Ligand 8 and interleukin-6 genes and the M2-to-M1 reprogramming of these cells upon levan treatment. Finally, cytokine release studies confirm that hydrolyzed levans increase the secretion of pro-inflammatory cytokines and reprogram IL-4-polarized macrophages to the M1 state. Overall findings indicate that Halomonas levans trigger a classical macrophage activation and pave the way for their application in therapeutic interventions requiring a pro-inflammatory phenotype.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Organik Kimya; Fizik Bilimleri; Polimerler ve Plastikler; Malzeme Kimyası; Organic Chemistry; Physical Sciences; Polymers and Plastics; Materials Chemistry; Classical (M1) and alternative (M2) macrophage activation; Fructan; Halomonas levan; Immunotherapy; Macrophage polarization; RNA-seq